Peran Pemerintah Daerah dalam Pemberdayaan UMKM Orang Asli Papua (OAP) di Kabupaten Biak Numfor - Salehuddin Salehuddin; Rani Maswati; Samar Samar (Universitas Indraprasta PGRI, 2021)
The role of government in community empowerment is very much needed. This study aims to determine the role of the government in empowering MSMEs of indigenous Papuans in the Biak Numfor Regency. This research is a qualitative descriptive study. In an effort to present a comprehensive understanding, this research uses a qualitative approach. The techniques used in collecting data in this study include; observation, interview, and documentation. The data analysis in this research is using qualitative descriptive data analysis. The results of the study indicate that the role of the government in empowering MSMEs of indigenous Papuans in Biak Numfor Regency is through training, business capital assistance, promotion and marketing assistance, and production equipment assistance. The inhibiting factors in empowering MSMEs of indigenous Papuans in Biak Numfor Regency are the lack of entrepreneurial knowledge and lack of facilities and infrastructure.